Secondary battery and device including said secondary battery

By integrating specific active materials and controlled surface smoothness in the electrode sheets, the secondary battery achieves improved low-temperature power and high-temperature cycle performance while maintaining high energy density.

JP7657216B2Active Publication Date: 2025-04-04CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022532164
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-27
Publication Date
2025-04-04
Estimated Expiration
2040-03-27

AI Technical Summary

Technical Problem

Secondary batteries face challenges in achieving high energy density while maintaining good low-temperature power performance and high-temperature cycle performance.

Method used

The secondary battery design incorporates a positive electrode sheet with a specific active material, a negative electrode sheet with artificial and natural graphite, and a controlled surface smoothness of the negative electrode film sheet within a specific range, optimizing the active ion transport and energy density.

Benefits of technology

This design effectively improves the low-temperature power performance of the secondary battery while maintaining high energy density and reducing high-temperature cycle expansion, thereby enhancing the overall performance and longevity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657216000003
    Figure 0007657216000003
  • Figure 0007657216000004
    Figure 0007657216000004
  • Figure 0007657216000005
    Figure 0007657216000005
Patent Text Reader

Abstract

The present application discloses a secondary battery and a device including the secondary battery. The secondary battery includes a positive electrode sheet and a negative electrode sheet. The positive electrode sheet includes a positive electrode current collector and a positive electrode film sheet disposed on at least one surface of the positive electrode current collector and having a positive electrode active material. The negative electrode sheet includes a negative electrode current collector and a negative electrode film sheet disposed on at least one surface of the negative electrode current collector and having a negative electrode active material. The negative electrode active material includes a first material having artificial graphite and a second material having natural graphite. The positive electrode active material includes one or more types of layered lithium transition metal oxides and modified compounds thereof. The smoothness L of the surface of the negative electrode film sheet facing the negative electrode current collector satisfies 40≦L≦50. Alternatively, the positive electrode active material includes one or more types of lithium-containing phosphates with an olivine structure and modified compounds thereof. The smoothness L of the surface of the negative electrode film sheet facing the negative electrode current collector satisfies 45≦L≦55.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery and an apparatus including the secondary battery. [Background technology]

[0002] Secondary batteries have the advantages of reliable operation performance, no pollution, no memory effect, etc., and are therefore widely used. For example, with the increasing emphasis on environmental protection issues, new energy vehicles are becoming more and more popular, and the demand for power-type secondary batteries is growing explosively. However, as the application range of secondary batteries becomes wider, high requirements are placed on the low-temperature power performance and energy density of secondary batteries. The low low-temperature power performance of secondary batteries affects their use in low-temperature environments. The energy density affects the battery's range performance, that is, the usage time after one charge. Therefore, how to improve the low-temperature power performance of secondary batteries on the premise of having high energy density has become a technical problem that needs to be solved urgently. Summary of the Invention

[0003] A first aspect of the present application provides a secondary battery comprising a positive electrode sheet and a negative electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode film sheet disposed on at least one surface of the positive electrode current collector and having a positive electrode active material, and the negative electrode sheet comprising a negative electrode current collector and a negative electrode film sheet disposed on at least one surface of the negative electrode current collector and having a negative electrode active material, wherein the positive electrode active material comprises one or more types of layered lithium transition metal oxides and modified compounds thereof, the negative electrode active material comprises a first material having artificial graphite and a second material having natural graphite, and the smoothness L of a surface of the negative electrode film sheet facing the negative electrode current collector satisfies 40≦L≦50, preferably satisfies 43≦L≦48.

[0004] A second aspect of the present application provides a secondary battery comprising a positive electrode sheet and a negative electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode film sheet disposed on at least one surface of the positive electrode current collector and having a positive electrode active material, and the negative electrode sheet comprising a negative electrode current collector and a negative electrode film sheet disposed on at least one surface of the negative electrode current collector and having a negative electrode active material, wherein the positive electrode active material comprises one or more of lithium-containing phosphates having an olivine structure and modified compounds thereof, the negative electrode active material comprises a first material having artificial graphite and a second material having natural graphite, and the smoothness L of the surface of the negative electrode film sheet facing the negative electrode current collector satisfies 45≦L≦55, preferably satisfies 48≦L≦52.

[0005] A third aspect of the present application provides an apparatus including the secondary battery according to the first aspect of the present application.

[0006] Surprisingly, it has been found that in the secondary battery of the present application, the positive electrode sheet uses a specific positive electrode active material, the negative electrode active material of the negative electrode sheet has both artificial graphite and natural graphite, and the smoothness of the surface facing the negative electrode current collector in the negative electrode film sheet is controlled within a specific range, so that the negative electrode sheet has a high energy density and at the same time the active ion transport performance of the negative electrode sheet can be effectively improved, so that the secondary battery can have good low-temperature power performance on the premise of having a high energy density. More preferably, the secondary battery can also have low high-temperature cycle expansion and high high-temperature cycle capacity retention at the same time. The device of the present application is equipped with the secondary battery of the present application, and therefore has at least the same advantages as the secondary battery. [Brief description of the drawings]

[0007] In the following, in order to more clearly explain the technical solutions of the embodiments of the present application, drawings necessary for the embodiments of the present application will be briefly introduced. Of course, the drawings described below are only some of the embodiments of the present application, and those skilled in the art can further obtain other drawings based on the drawings without any creative work.

[0008] [Figure 1] FIG. 1 is a schematic diagram of an embodiment of a secondary battery. [Diagram 2] FIG. 2 is an exploded view of FIG. [Diagram 3] FIG. 1 is a schematic diagram of one embodiment of a battery module. [Figure 4] FIG. 1 is a schematic diagram of one embodiment of a battery pack. [Diagram 5] FIG. 5 is an exploded view of FIG. [Figure 6] FIG. 1 is a schematic diagram of an embodiment of a device in which a secondary battery is used as a power source. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] In order to make the inventive objectives, technical solutions and beneficial technical effects of the present application clearer, the present application will be described in detail in conjunction with examples. It should be understood that the examples described herein are merely for interpreting the present application, and are not intended to limit the present application.

[0010] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit may be combined with any upper limit to form a range not explicitly described, and any lower limit may be combined with any other lower limit to form a range not explicitly described, and similarly, any upper limit may be combined with any other upper limit to form a range not explicitly described. Also, although not explicitly described, each point or single value between the endpoints of a range is included within the range. Thus, each point or single value may be combined with any other point or single value as its own lower limit or upper limit, or combined with any other lower limit or upper limit to form a range not explicitly described.

[0011] It should be noted that in the description of this specification, unless otherwise specified, "more than" and "less than" are inclusive of the target number, and "multiple types" in "one type or multiple types" means two types or more than two types.

[0012] The above summary of the invention of this application is not intended to describe each embodiment or every implementation disclosed herein. The following description more particularly illustrates and describes exemplary embodiments. Throughout this application, guidance is provided through a series of examples that can be used in various combinations. In each example, the enumeration is used only as a representative group and should not be interpreted as exhaustive. secondary battery

[0013] A first aspect of the present application provides a secondary battery. The secondary battery includes a positive electrode sheet, a negative electrode sheet, and an electrolyte. During the charge and discharge process of the battery, active ions are inserted and removed between the positive electrode sheet and the negative electrode sheet. The electrolyte serves to conduct ions between the positive electrode sheet and the negative electrode sheet. [Positive electrode sheet]

[0014] The positive electrode sheet includes a positive electrode current collector and a positive electrode film sheet disposed on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two surfaces opposed to each other in the thickness direction, and the positive electrode film sheet is laminated to any one or both of the two surfaces of the positive electrode current collector.

[0015] The positive electrode current collector can be made of a material having good electrical conductivity and mechanical strength to perform the functions of electrical conductivity and current collection. In some embodiments, the positive electrode current collector can be made of aluminum foil.

[0016] The positive electrode film sheet has a positive electrode active material. The positive electrode active material can be any positive electrode active material for secondary batteries known in the art. In some embodiments, the positive electrode active material can include one or more of layered lithium transition metal oxides, lithium-containing phosphates with olivine structure, and modified compounds of the above materials.

[0017] The "modification" in the "modifying compound" may be a doping modification and / or a surface coating modification to the material.

[0018] In some embodiments, the positive electrode active material includes one or more of layered lithium transition metal oxides and modified compounds thereof. As specific examples, the positive electrode active material includes, but is not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and modified compounds thereof. Preferably, the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and modified compounds thereof.

[0019] In some embodiments, the positive electrode active material is Li a Ni b Co c M d M’ e O f A g and Li having a coating layer on at least a part of the surface a Ni b Co c M d M’ e O f A g including one or more of them. Among them, 0.8 ≦ a ≦ 1.2, 0.5 ≦ b < 1, 0 < c < 1, 0 < d < 1, 0 ≦ e ≦ 0.1, 1 ≦ f ≦ 2, 0 ≦ g ≦ 1, M is selected from one or more of Mn and Al, M’ is selected from one or more of Zr, Al, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, preferably includes one or more of Zr, Al, Zn, and B, and A is selected from one or more of N, F, S, and Cl.

[0020] In some embodiments, M is selected from Mn and M′ is selected from one or more of Zr, Al, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, preferably one or more of Zr, Al, Zn, and B. Or, M is selected from Al and M′ is selected from one or more of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, preferably one or more of Zr, Zn, and B.

[0021] The positive electrode active material, by including a high-nickel ternary positive electrode active material, has a higher capacity per gram, thereby increasing the energy density of the battery.

[0022] In some embodiments, Li a Ni b Co c M d M' e O f A g The particles may have a coating layer on 80% to 100% of the surface. a Ni b Co c M d M' e O f A g The particles may have a coating layer on 90% to 100% of the surface.

[0023] In some other embodiments, the positive electrode active material comprises one or more of the following lithium-containing phosphates with an olivine structure and modified compounds thereof. Examples of the lithium-containing phosphates with an olivine structure include, but are not limited to, one or more of the following lithium iron phosphates, lithium iron phosphate-carbon composites, lithium manganese phosphates, lithium manganese phosphate-carbon composites and modified compounds thereof.

[0024] The composite material of lithium iron phosphate and carbon may be one or more of a coating type composite material and an insertion type composite material. The coating type composite material has a carbon coating layer on at least a part of the surface of the lithium iron phosphate particles. For example, the carbon coating layer coats 80% to 100% (e.g., 90% to 100%) of the surface of the lithium iron phosphate particles. The carbon coating layer may include one or more of graphite, hard carbon, soft carbon, carbon black, coke, etc. The insertion type composite material has lithium iron phosphate dispersed in a carbon support. The carbon support may include one or more of graphite, hard carbon, soft carbon, carbon black, coke, etc.

[0025] The composite material of lithium manganese phosphate and carbon may be one or more of a coating type composite material and an insertion type composite material. The coating type composite material has a carbon coating layer on at least a part of the surface of the lithium manganese phosphate particles. For example, the carbon coating layer coats 80% to 100% (e.g., 90% to 100%) of the surface of the lithium manganese phosphate particles. The carbon coating layer may include one or more of graphite, hard carbon, soft carbon, carbon black, coke, etc. The insertion type composite material has lithium manganese phosphate dispersed in a carbon support. The carbon support may include one or more of graphite, hard carbon, soft carbon, carbon black, coke, etc.

[0026] In some embodiments, the positive electrode film sheet further optionally includes an adhesive. The type of adhesive is not particularly limited, and can be selected by those skilled in the art according to actual needs. For example, the adhesive for the positive electrode film sheet can include one or more of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).

[0027] In some embodiments, the positive electrode film sheet further includes a conductive agent. The type of the conductive agent is not particularly limited, and can be selected by those skilled in the art according to actual needs. For example, the conductive agent for the positive electrode film sheet can include one or more of graphite, superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. [Negative electrode sheet]

[0028] The negative electrode sheet includes a negative electrode current collector and a negative electrode film sheet disposed on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two surfaces opposed to each other in the thickness direction, and the negative electrode film sheet is laminated to any one or both of the two surfaces of the negative electrode current collector.

[0029] The negative electrode current collector can be made of a material having good electrical conductivity and mechanical strength to perform the functions of electrical conductivity and current collection. In some embodiments, the negative electrode current collector can be made of copper foil.

[0030] The negative electrode film sheet has a negative electrode active material, the negative electrode active material including a first material having artificial graphite and a second material having natural graphite. Surprisingly, it has been found that when the smoothness L of the surface facing the negative electrode current collector in the negative electrode film sheet is controlled within a specific range, the negative electrode sheet has a high energy density and at the same time effectively improves the active ion transport performance of the negative electrode sheet, so that the secondary battery using it has a high energy density and improves low-temperature power performance. More preferably, the secondary battery can also have low high-temperature cycle expansion and high high-temperature cycle capacity retention at the same time.

[0031] The smoothness L represents the roughness of the surface of the negative electrode film sheet facing the negative electrode current collector. The smoothness L can be set within a desired range by adjusting one or more of the following: the selection type of the first material, the selection type of the second material, the ratio of the first material to the second material, the occupancy rate of natural graphite, the compressed density of the negative electrode film sheet, the type of conductive agent, the content of the conductive agent, etc. The selection types of the first material and the second material each separately include, but are not limited to, one or more of their composition, graphitization degree, particle size distribution, surface coating modification, etc.

[0032] The inventors have further found that by co-designing the negative electrode sheet in combination with the positive electrode active material used in the battery, the secondary battery can exhibit better performance. The inventors have found through intensive research that when the positive electrode active material of the positive electrode sheet includes one or more types of layered lithium transition metal oxides and their modified compounds, the surface smoothness L of the negative electrode film sheet facing the negative electrode current collector satisfies 40≦L≦50.

[0033] When the positive electrode active material includes one or more kinds of layered lithium transition metal oxides and their modified compounds, the negative electrode active material of the negative electrode sheet includes artificial graphite and natural graphite at the same time, and the smoothness L of the negative electrode film sheet satisfies 40≦L≦50, the positive electrode active material and the negative electrode active material can be effectively combined, and the synergistic effect of the advantages of both materials can be fully exerted, and under the premise of ensuring that the battery has high energy density, the negative electrode sheet can further form a surface porosity suitable for electrolyte infiltration, and the solid-phase diffusion rate of active ions in the negative electrode can be improved, so that the transport performance of active ions between the positive electrode and the negative electrode can be further improved. This significantly improves the dynamic performance of the battery, and even in a low-temperature environment, the negative electrode can quickly receive active ions from the positive electrode, so that the low-temperature power performance of the secondary battery can be improved. The secondary battery is suitable for high-rate charging and discharging, and can obviously reduce the probability of lithium precipitation during high-rate charging at low temperatures, and at the same time, can ensure that the secondary battery has high safety performance. In addition, the positive electrode active material contains one or more of the layered lithium transition metal oxides and modified compounds thereof, which allows the positive electrode sheet to have a high areal density (e.g., 14 mg / cm 2 ~20mg / cm 2 ) and compressed density (e.g. 3.3g / cm 3 ~3.5g / cm 3 ), the battery can have a high energy density.

[0034] In these embodiments, more preferably, the positive electrode active material comprises one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and its modified compounds, which can better exert the above-mentioned effects.

[0035] The inventors further found that when the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and modified compounds thereof, the negative electrode active material has both artificial graphite and natural graphite, and the smoothness L of the negative electrode film sheet satisfies 40≦L≦50, the negative electrode sheet can have high cohesive strength and adhesive strength, further reduce the expansion of the negative electrode during the battery cycle process, and improve the electrolyte retention ability of the electrode sheet, thereby maintaining a high volumetric energy density and further improving the dynamic performance.

[0036] In addition, since the negative electrode sheet has high ion and electron transport performance, the battery can have low resistance. In addition, the negative electrode sheet contains artificial graphite and natural graphite at the same time, and the smoothness L of the negative electrode film sheet satisfies 40≦L≦50, for example, L is 40.5, 41.6, 42.3, 43.5, 44.8, 45.5, 46.0, 46.5, 47.0, 47.5, 48.0, 48.5 or 49.7, thereby reducing the loss of active material due to poor contact of particles and / or reducing the battery polarization phenomenon due to uneven distribution of electrolyte. Therefore, the battery can also achieve a high high-temperature cycle capacity retention rate.

[0037] In these embodiments, preferably, 43≦L≦48. When the smoothness L of the negative electrode film sheet is within an appropriate range, the low-temperature power performance of the battery can be further improved, the high-temperature cycle expansion of the battery can be further reduced, and the high-temperature cycle capacity retention rate of the battery can be further increased.

[0038] Through further research, the inventors have found that when the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and its modified compounds, the negative electrode active material includes artificial graphite and natural graphite at the same time, and the smoothness L of the negative electrode film sheet satisfies 40≦L≦50, if the negative electrode active material further satisfies one or more of the following conditions, the performance of the battery can be further improved:

[0039] In some preferred embodiments, the mass occupancy of natural graphite in the negative electrode active material may be 10% to 50%, preferably 15% to 30%, more preferably 15% to 25%, for example, 15%, 17%, 19%, 20%, 21%, 23%. When the negative electrode active material contains an appropriate amount of natural graphite, the negative electrode active material can have a high capacity per gram, and in particular, the ion solid-phase diffusion rate of the negative electrode sheet can be further increased, so that the battery has a high energy density and the power performance of the battery can be further improved. In addition, an appropriate amount of natural graphite improves the adhesive strength between the particles of the negative electrode active material and between the negative electrode active material and the negative electrode current collector, so that the negative electrode sheet has high cohesive strength and adhesive strength, and at the same time, the side reaction on the negative electrode surface is reduced, so that the battery has low high-temperature cycle expansion. The high-temperature cycle performance of the battery can also be further improved.

[0040] In some preferred embodiments, the powder compaction density of the negative electrode active material under a pressure of 30,000 N is 1.7 g / cm 3 ~1.9g / cm 3 and preferably 1.75 g / cm 3 ~1.85g / cm 3 When the powder compaction density of the negative electrode active material is within a suitable range, the negative electrode film sheet can have a high compaction density, thereby increasing the energy density of the battery.

[0041] In order to set the powder compaction density of the negative electrode active material within the above-mentioned predetermined range, in some preferred embodiments, the powder compaction density of natural graphite under a pressure of 30,000 N is preferably 1.75 g / cm 3 ~1.9g / cm 3 and more preferably 1.75 g / cm 3 ~1.85g / cm 3 The powder compaction density of the artificial graphite under a pressure of 30,000 N is preferably 1.7 g / cm 3 ~1.9g / cm 3 and more preferably 1.8 g / cm 3 ~1.9g / cm3 It is.

[0042] In some preferred embodiments, the graphitization degree of the negative electrode active material may be 92% to 96%, preferably 93% to 95%. When the graphitization degree of the negative electrode active material is within a suitable range, it has a small powder resistivity, which reduces the resistance of the negative electrode sheet, and at the same time, has a layer spacing suitable for ion insertion and desorption, so that the low-temperature power performance of the battery can be further improved. In addition, the negative electrode sheet using the negative electrode active material further has high cohesive strength and adhesive strength, which can improve the low-cycle expansion performance of the battery.

[0043] The inventors further found that when the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and modified compounds thereof, the negative electrode active material includes artificial graphite and natural graphite, and the smoothness L of the negative electrode film sheet is within a certain range, the graphitization degree of the negative electrode active material can be set within the above range, and the high temperature cycle performance of the battery can also be improved.

[0044] In order to set the graphitization degree of the negative electrode active material within the above-mentioned predetermined range, in some preferred embodiments, the graphitization degree of the natural graphite may be 95% to 98.5%, preferably 96% to 98%, and more preferably 96.5% to 97.6%, and the graphitization degree of the artificial graphite may be 90% to 97.5%, preferably 90% to 95%, and more preferably 91% to 93.5%.

[0045] In some preferred embodiments, the volume average particle size D of the negative electrode active material v The diameter of the negative electrode active material may be 10 μm to 18 μm, preferably 11 μm to 15 μm, and more preferably 12 μm to 14 μm. vThe smaller the D50, the more surface particles of the negative electrode film sheet, the greater the rebound of the electrode sheet after cold pressing, the greater the surface particles are intercalated with each other, and the greater the surface roughness, so that the surface smoothness of the negative electrode film sheet is small, which can increase the infiltration of the electrolyte and the migration rate of ions in the negative electrode film sheet. v When 50 is appropriate, the negative electrode film sheet can have a high active ion migration rate, while at the same time improving the capacity per gram of the negative electrode active material and reducing the surface active sites of the electrode sheet, thereby improving the low-temperature power performance, energy density and high-temperature cycle performance of the battery.

[0046] Negative electrode active material D v In order to make the D 50 within the above-mentioned range, in some preferred embodiments, the D v 50 may be 10 μm to 16 μm, preferably 10 μm to 14 μm, more preferably 11 μm to 13 μm, and D of the artificial graphite v 50 may be from 12 μm to 19 μm, preferably from 12 μm to 16 μm, and more preferably from 13 μm to 15 μm.

[0047] In some preferred embodiments, the negative electrode film sheet has a compressed density of 1.6 g / cm 3 ~1.8g / cm 3 and preferably 1.65 g / cm 3 ~1.75g / cm 3 and particularly preferably 1.68 g / cm 3 ~1.73g / cm 3When the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and its modified compounds, the negative electrode active material includes artificial graphite and natural graphite, the smoothness L of the negative electrode film sheet is within a certain range, and the compression density of the negative electrode film sheet is within a certain range, it can ensure that the battery has a high energy density, and at the same time, the negative electrode film sheet has high electrolyte infiltration and good ion solid-phase diffusion rate, so as to further improve the power performance of the battery. In addition, the appropriate compression density can also protect the integrity of the particle structure of the negative electrode active material, improve the cohesion and adhesion of the negative electrode sheet, and is favorable to reduce the expansion and side reactions during the high-temperature cycle of the battery, so as to further improve the high-temperature cycle life of the battery.

[0048] In some preferred embodiments, the areal density of the negative electrode film sheet is 10 mg / cm 2 ~13mg / cm 2 and preferably 10.5 mg / cm 2 ~11.5mg / cm 2 When the positive electrode material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and its modified compounds, the negative electrode active material includes artificial graphite and natural graphite, the smoothness L of the negative electrode film sheet is within a certain range, and the surface density of the negative electrode film sheet is within a certain range, the battery can have a high energy density. At the same time, the battery has better ion and electron transport performance, which further improves the dynamic performance of the battery. In addition, when the battery meets the above design, the polarization and side reactions can be reduced, which further improves the high temperature cycle performance of the battery.

[0049] The inventors further found that when the positive electrode active material of the positive electrode sheet includes one or more of the lithium-containing phosphates having an olivine structure and modified compounds thereof, the surface smoothness L of the negative electrode film sheet facing the negative electrode current collector preferably satisfies 45≦L≦55.

[0050] When the positive active material comprises one or more of the lithium-containing phosphates with olivine structure and their modified compounds, the negative active material of the negative sheet comprises artificial graphite and natural graphite at the same time, and the smoothness L of the negative film sheet satisfies 45≦L≦55, the positive active material and the negative active material form an effective combination, fully exert the synergistic effect of the advantages of both, and under the premise of ensuring that the battery has high energy density, the solid-phase diffusion rate of the active ions between the positive and negative electrodes is improved, so that the dynamic performance of the battery is further improved, and even in a low-temperature environment, the negative electrode can rapidly receive the active ions from the positive electrode, so that the low-temperature power performance of the secondary battery can be improved. This secondary battery is suitable for high-rate charging and discharging, and obviously reduces the probability of lithium precipitation occurring when high-rate charging is performed at low temperatures.

[0051] In these embodiments, it is more preferable that the positive electrode active material includes one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, and a modified compound thereof, so as to better exert the above-mentioned effects.

[0052] The inventors further found that when the positive electrode active material includes one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, and modified compounds thereof, and the negative electrode active material includes both artificial graphite and natural graphite, and the smoothness L of the negative electrode film sheet satisfies 45≦L≦55, the expansion during the battery cycle can be further reduced, and the electrolyte retention capacity between the active materials in the electrode sheet can be increased, which is advantageous for maintaining a high volumetric energy density and improving the dynamic performance at the same time.

[0053] In addition, the negative electrode sheet has high ion and electron transport performance, so that the battery can have low resistance. In addition, the negative electrode sheet contains both artificial graphite and natural graphite, and the smoothness L of the negative electrode film sheet satisfies 45≦L≦55, so that the loss of active material due to poor contact of particles can be reduced, and / or the battery polarization phenomenon due to uneven distribution of electrolyte can be reduced. Therefore, the battery can also achieve a high high-temperature cycle capacity retention rate.

[0054] In these embodiments, more preferably, 48≦L≦52. For example, L is 48.5, 49.0, 49.5, 50.0, 50.5, 51.0 or 51.5. When the smoothness L of the negative electrode film sheet is within an appropriate range, the low-temperature power performance of the battery can be further improved, the high-temperature cycle expansion of the battery can be further reduced, and the high-temperature cycle capacity retention rate of the battery can be further increased.

[0055] Through further research, the inventors have found that when the positive electrode active material comprises one or more of the following lithium-containing phosphates with olivine structure and their modified compounds, the negative electrode active material comprises both artificial graphite and natural graphite, and the smoothness L of the negative electrode film sheet satisfies 45≦L≦55, if the negative electrode active material further satisfies one or more of the following conditions, the performance of the battery can be further improved:

[0056] In some preferred embodiments, the mass occupancy of natural graphite in the negative electrode active material may be 10% to 50%, preferably 15% to 50%, more preferably 35% to 50%, for example, 30%, 35%, 40%, 42%, 45%, 48% or 50%. When the negative electrode active material contains an appropriate amount of natural graphite, the negative electrode active material can have a high capacity per gram, and in particular, the ion solid-phase diffusion rate of the negative electrode sheet can be further increased, so that the battery has a high energy density and the power performance of the battery can be further improved. In addition, an appropriate amount of natural graphite improves the adhesive strength between the particles of the negative electrode active material and between the negative electrode active material and the negative electrode current collector, so that the negative electrode sheet has high cohesive strength and adhesive strength, and at the same time, the side reaction on the negative electrode surface is reduced, so that the battery has low high-temperature cycle expansion. The high-temperature cycle performance of the battery can also be further improved.

[0057] In some preferred embodiments, the powder compaction density of the negative electrode active material at 30,000 N pressure is preferably 1.8 g / cm 3 ~1.9g / cm 3 and more preferably 1.82 g / cm 3 ~1.88g / cm 3 When the powder compaction density of the negative electrode active material is within a suitable range, the negative electrode film sheet can have a high compaction density, thereby increasing the energy density of the battery.

[0058] In order to make the powder compaction density of the negative electrode active material fall within the above-mentioned range, in some preferred embodiments, the powder compaction density of natural graphite under a pressure of 30,000 N is preferably 1.85 g / cm 3 ~1.95g / cm 3 and more preferably 1.90 g / cm 3 ~1.95g / cm 3 The powder compaction density of artificial graphite under 30,000N pressure is 1.75g / cm 3 ~1.85g / cm 3 and more preferably 1.77 g / cm 3 ~1.80g / cm 3 It is.

[0059] In some preferred embodiments, the graphitization degree of the negative electrode active material is 92%-95%, preferably 93%-94%. When the graphitization degree of the negative electrode active material is within a suitable range, it has a small powder resistivity, which reduces the resistance of the negative electrode sheet, and at the same time, has a layer spacing suitable for ion insertion and desorption, so that the low-temperature power performance of the battery can be further improved. In addition, the negative electrode sheet using the negative electrode active material also has high cohesive strength and adhesive strength, which can improve the low-cycle expansion performance of the battery.

[0060] The inventors further found that when the positive electrode active material comprises one or more of the lithium-containing phosphates with olivine structure and their modified compounds, the negative electrode active material comprises artificial graphite and natural graphite, the smoothness L of the negative electrode film sheet is within a certain range, and the graphitization degree of the negative electrode active material is within the above range, the high temperature cycle performance of the battery can also be improved.

[0061] In order to make the graphitization degree of the negative electrode active material fall within the above-mentioned predetermined range, in some preferred embodiments, the graphitization degree of the natural graphite may be 95% to 98.5%, preferably 97.5% to 98.5%, and the graphitization degree of the artificial graphite may be 89% to 95%, preferably 90% to 93%.

[0062] In some preferred embodiments, the volume average particle size D of the negative electrode active material v 50 is 15 μm to 19 μm, preferably 16 μm to 18 μm. v The smaller the D50, the more pores there are on the surface of the negative electrode film sheet, and the smaller the surface smoothness of the negative electrode film sheet, which can increase the infiltration of the electrolyte and the migration rate of the active ions in the negative electrode film sheet. vWhen 50 is appropriate, the negative electrode film sheet can have a high ion transfer rate, while at the same time improving the capacity per gram of the negative electrode active material and reducing the surface active sites of the electrode sheet, thereby improving the low-temperature power performance, energy density and high-temperature cycle performance of the battery.

[0063] D of negative electrode active material v In order to make the D 50 within the above-mentioned range, in some preferred embodiments, the D v 50 may be 15 μm to 20 μm, preferably 15 μm to 19 μm, more preferably 16 μm to 18 μm, and D of the artificial graphite v 50 may be 14 μm to 19 μm, preferably 14 μm to 18 μm, and more preferably 15 μm to 17 μm.

[0064] In some preferred embodiments, the negative electrode film sheet has a compressed density of 1.5 g / cm 3 ~1.7g / cm 3 and preferably 1.55 g / cm 3 ~1.65g / cm 3 When the positive electrode active material includes one or more of lithium-containing phosphates with olivine structure and their modified compounds, the negative electrode active material includes artificial graphite and natural graphite at the same time, the smoothness L of the negative electrode film sheet is within a certain range, and the compression density of the negative electrode film sheet is within a certain range, it can ensure that the battery has a high energy density, and at the same time, the negative electrode film sheet has high electrolyte infiltration and good ion solid-phase diffusion rate, so as to further improve the low-temperature power performance of the battery. In addition, the appropriate compression density can also protect the integrity of the particle structure of the negative electrode active material, improve the cohesive strength and adhesive strength of the negative electrode sheet, and is favorable to reduce the expansion and side reactions during the high-temperature cycle process of the battery, so as to further improve the high-temperature cycle life of the battery.

[0065] In some preferred embodiments, the areal density of the negative electrode film sheet is 7 mg / cm 2 ~10mg / cm 2and preferably 7 mg / cm 2 ~8mg / cm 2 When the positive electrode material includes one or more of olivine-structured lithium-containing phosphates and their modified compounds, the negative electrode active material includes artificial graphite and natural graphite, the smoothness L of the negative electrode film sheet is within a certain range, and the surface density of the negative electrode film sheet is within a certain range, the battery can have a high energy density. At the same time, the battery has better ion and electron transport performance, which further improves the dynamic performance of the battery. In addition, when the battery meets the above design, the polarization and side reactions can be reduced, which further improves the high-temperature cycle performance of the battery.

[0066] In any negative electrode sheet of the present application, the negative electrode active material may optionally further include one or more of hard carbon, soft carbon, silicon-based material, and tin-based material. The silicon-based material may be selected from one or more of silicon alone, silicon oxygen compounds, silicon carbon composites, and silicon alloys. The tin-based material may be selected from one or more of tin alone, tin oxygen compounds, and tin alloys.

[0067] In some embodiments, the negative electrode film sheet may further include an adhesive. For example, the adhesive for the negative electrode film sheet may be selected from one or more of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene butadiene rubber (SBR), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0068] In some embodiments, the negative electrode film sheet optionally further comprises a thickener. For example, the thickener may be sodium carboxymethylcellulose (CMC-Na).

[0069] In some embodiments, the negative electrode film sheet further optionally includes a conductive agent. For example, the conductive agent for the negative electrode film sheet can be selected from one or more of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0070] In this application, the smoothness L of the negative electrode film sheet has a well-known meaning in the art and can be measured by a method known in the art. An exemplary measurement method is as follows. First, the negative electrode sheet is placed under the measurement port of a precision color difference meter (e.g., a multi-function precision color difference meter NR60CP), the measurement port of the precision color difference meter is brought close to the negative electrode film sheet and the position is adjusted to achieve alignment, measurement is performed, and the measurement results are recorded. In order to ensure the accuracy of the measurement results, 10 groups of test samples are taken, and the average value of the 10 groups of test samples is calculated.

[0071] In this application, the powder compaction density of the negative active material has a well-known meaning in the art and can be measured by a method known in the art. For example, it can be measured by using an electronic pressure tester (for example, UTM7305) with reference to GB / T 24533-2009. An exemplary measurement method is as follows: Put a test powder with mass M into a special compaction mold (bottom area S), set different pressures (30000N is used in this application), hold the pressure for 30 s, then release the pressure, wait for 10 s, read the thickness H of the powder compacted under the pressure by the instrument, and the powder compaction density of the negative active material under the pressure=M / (H×S).

[0072] In this application, the areal density of the negative electrode film sheet has a meaning well known in the art and can be measured by a method well known in the art. For example, take a negative electrode sheet after one side coating and cold pressing (if it is a double-sided coated electrode sheet, one side of the negative electrode film sheet can be wiped first), punch it into a small circular sheet with an area S1, weigh it, and record it as M1. Next, wipe off the negative electrode film sheet of the weighed negative electrode sheet, weigh the weight of the negative electrode current collector, and record it as M0, and the areal density of the negative electrode film sheet = (weight of the negative electrode sheet M1 - weight of the negative electrode current collector M0) / S1.

[0073] In this application, the compression density of the negative electrode film sheet has a well-known meaning in this field and can be measured by a method known in this field. For example, take the negative electrode sheet after one-sided coating and cold pressing (if the electrode sheet is coated on both sides, one side of the negative electrode film sheet can be wiped first), measure the thickness of the negative electrode film sheet, and then measure the surface density of the negative electrode film sheet according to the above method, where the compression density of the negative electrode film sheet=the surface density of the negative electrode film sheet / the thickness of the negative electrode film sheet.

[0074] In this application, the negative electrode active material D v D 50 has a well-known meaning in the art and can be measured by methods known in the art, for example, by referring to standard GB / T 19077.1-2016 and using a laser particle size analyzer (e.g., Malvern Master Size 3000). v The physical definition of 50 is the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%.

[0075] In the present application, the graphitization degree of the negative electrode active material has a meaning well known in the art and can be measured by a method known in the art. For example, it can be measured using an X-ray diffractometer (e.g., Bruker D8 Discover). The measurement can be performed by referring to JIS K 0131-1996 and JB / T 4220-2011. 002 After measuring the size of the002 ) / (0.344-0.3354)×100%, the graphitization degree can be calculated, of which d 002 is the layer spacing in the graphite crystal structure calculated in nm. α The radiation source was radiation, the radiation wavelength was λ=1.5418 Å, the scanning 2θ angle range was 20° to 80°, and the scanning speed was 4° / min. [Electrolyte]

[0076] The electrolyte is located between the positive electrode sheet and the negative electrode sheet and serves to conduct ions. The present application does not particularly limit the type of electrolyte, and it can be selected according to the needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolytic solution).

[0077] In some embodiments, the electrolyte is a liquid electrolyte, which includes an electrolyte salt and a solvent.

[0078] In some embodiments, the electrolyte salt can be selected from one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bisfluorosulfonylimide), LiTFSI (lithium bis(trifluoromethanesulfonate)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluoro(oxalato)borate), LiBOB (lithium bisoxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalato)phosphate), and LiTFOP (lithium tetrafluorooxalatophosphate).

[0079] In some embodiments, the solvent may be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0080] In some embodiments, the electrolyte solution further selectively includes an additive. For example, the additive may include an additive for forming a negative electrode film, an additive for forming a positive electrode film, or an additive that can improve a specific performance of the battery, such as an additive for improving the overcharge performance of the battery, an additive for improving the high temperature performance of the battery, or an additive for improving the low temperature performance of the battery. [Separator]

[0081] In secondary batteries using an electrolyte solution and some secondary batteries using a solid electrolyte, a separator is further included. The separator is disposed between the positive electrode sheet and the negative electrode sheet to perform the function of isolation. The present application does not particularly limit the type of separator, and any separator with a well-known porous structure having good chemical stability and mechanical stability can be selected. In some embodiments, the material of the separator can be selected from one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different.

[0082] The present application does not particularly limit the shape of the secondary battery, which may be cylindrical, rectangular, or any other shape. Figure 1 shows a secondary battery 5 having a rectangular structure as an example.

[0083] In some embodiments, the secondary battery may include an outer casing that is used to seal the positive electrode sheet, the negative electrode sheet, and the electrolyte.

[0084] In some embodiments, the exterior of the secondary battery may be a soft pack, for example, a bag-shaped soft pack. The material of the soft pack may be plastic, for example, one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc. The exterior of the secondary battery may be a hard case, for example, a hard plastic case, an aluminum case, a steel case, etc.

[0085] 2, in some embodiments, the exterior includes a case 51 and a cover plate 53. The case 51 includes a bottom plate and a side plate connected to the bottom plate, and a storage chamber is formed by being surrounded by the bottom plate and the side plate. The case 51 has an opening communicating with the storage chamber, and the cover plate 53 covers the opening to seal the storage chamber.

[0086] The positive electrode sheet, the negative electrode sheet, and the separator can be wound or laminated to form an electrode assembly 52. ​​The electrode assembly 52 is sealed in the chamber. An electrolyte can be an electrolytic solution, which is permeated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 can be one or more, and can be adjusted according to demand.

[0087] In some embodiments, the secondary batteries can be assembled to form a battery module, and the number of secondary batteries included in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0088] Fig. 3 shows an example of a battery module 4. Referring to Fig. 3, in the battery module 4, a plurality of secondary batteries 5 may be arranged sequentially along the length direction of the battery module 4. Of course, the batteries may be arranged in any other manner. Furthermore, the plurality of secondary batteries 5 may be fixed by a fastener.

[0089] Optionally, the battery module 4 further includes a case having an accommodating space, and the plurality of secondary batteries 5 are accommodated in the accommodating space.

[0090] In some embodiments, the battery modules can be further assembled to form a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0091] 4 and 5 show an example of a battery pack 1. Referring to Fig. 4 and Fig. 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 arranged in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 is arranged to cover the lower housing 3, and may form an enclosed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner. [Manufacturing method]

[0092] A method for manufacturing a secondary battery may include assembling a negative electrode sheet, a positive electrode sheet, and an electrolyte to form a secondary battery. In some embodiments, the positive electrode sheet, a separator, and a negative electrode sheet are wound or stacked sequentially, with the separator acting as an insulator between the positive and negative electrode sheets, to obtain an electrode assembly (i.e., a core). The core is placed into an outer casing, injected with electrolyte, and sealed to obtain a secondary battery.

[0093] In some embodiments, the manufacturing of the secondary battery may further include a step of manufacturing a positive electrode sheet. For example, a positive electrode active material, a conductive agent, and an adhesive may be dispersed in a solvent (e.g., N-methylpyrrolidone, abbreviated as NMP) to form a uniform positive electrode slurry. The positive electrode slurry is applied to a positive electrode current collector, and after processes such as drying and cold pressing, a positive electrode sheet is obtained.

[0094] In some embodiments, the manufacturing of the secondary battery may further include a step of manufacturing a negative electrode sheet. For example, the negative electrode active material, the adhesive, and optional thickener and conductive agent may be dispersed in a solvent to form a uniform negative electrode slurry, which may be deionized water. The negative electrode slurry is applied to a negative electrode current collector, and after a process such as drying and cold pressing, a negative electrode sheet is obtained. Device

[0095] A second aspect of the present application provides a device including the secondary battery according to the first aspect of the present application. The secondary battery may be used as a power source for the device, or may be used as an energy storage unit for the device. The device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0096] The device can select a secondary battery, a battery module or a battery pack according to the needs of its use.

[0097] An example device is shown in Figure 6. The device may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. A battery pack or a battery module may be used to meet the device's requirements for high power and high energy density of secondary batteries.

[0098] Other example devices may be mobile phones, tablets, notebook computers, etc. Such devices generally require light weight and thinness and may use secondary batteries as a power source. Working Example

[0099] The following examples will more specifically describe the contents of the present disclosure. These examples are merely illustrative, and such modifications and variations within the scope of the present disclosure will be obvious to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment. Additionally, the equipment used in the examples is commercially available. Example 1 Positive electrode sheet

[0100] Positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (abbreviated as NCM811), conductive agent Super P, adhesive PVDF are thoroughly stirred and mixed with an appropriate amount of NMP according to the mass ratio of 96.5:1.5:2 to form a homogeneous positive electrode slurry. The positive electrode slurry is applied to two surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained. Negative electrode sheet

[0101] The negative electrode active material (75% by weight of artificial graphite and 25% by weight of natural graphite), conductive agent Super P, adhesive SBR, thickener CMC-Na are thoroughly stirred and mixed with an appropriate amount of deionized water according to a mass ratio of 96.2:0.8:1.8:1.2 to form a homogeneous negative electrode slurry. The negative electrode slurry is applied to two surfaces of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained. Separator

[0102] Use a PP / PE composite separator. Electrolyte production

[0103] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte solution with a LiPF6 concentration of 1 mol / L. Secondary battery manufacturing

[0104] The positive electrode sheet, the separator, and the negative electrode sheet are sequentially stacked and wound to obtain an electrode assembly, which is then placed in an outer casing, into which the above-prepared electrolyte solution is injected, and after steps such as sealing, standing, chemical formation, and aging are carried out, a secondary battery is obtained. Examples 2 to 25 and Comparative Examples 1 to 12

[0105] The manufacturing method is similar to that of Example 1, and the difference is that the corresponding secondary batteries are obtained by adjusting the relevant parameters in the manufacturing process of the negative electrode sheet, and the details are shown in Tables 1 and 2. The batteries of Examples 1 to 12 and Comparative Examples 1 to 6 in Table 1 all use the positive electrode active material NCM811, and the positive electrode film sheet has a compressed density of 3.5 g / cm 3 and the surface density is 18.5mg / cm 2 The batteries of Examples 13 to 25 and Comparative Examples 7 to 12 in Table 2 all used lithium iron phosphate (abbreviated as LFP) as the positive electrode active material, and the positive electrode film sheet had a compressed density of 2.3 g / cm 3 and the surface density is 16.2mg / cm 2 It is. Test Part

[0106] In the following tests, when the positive electrode active material is lithium nickel cobalt manganese oxide, the discharge cut-off voltage is 2.8 V and the charge cut-off voltage is 4.2 V. When the positive electrode active material is lithium iron phosphate, the discharge cut-off voltage is 2.5 V and the charge cut-off voltage is 3.65 V. 1) Cyclic expansion rate test of negative electrode sheet

[0107] The initial thickness of the negative electrode sheet in each example and comparative example is denoted as H0. Next, in an environment of 25 ° C, a charge and discharge test is performed on the battery, and the battery is discharged at a constant current with a discharge current of 1.0C (i.e., a current value at which the theoretical capacity is completely discharged within 1 h) until the discharge cut-off voltage is reached. Thereafter, the battery is charged at a constant current with a charge current of 1.0C until the charge cut-off voltage is reached, and then the battery is charged at a constant voltage until the current becomes 0.05C, at which point the battery is in a fully charged state, i.e., 100% SOC (State of Charge). After leaving the fully charged battery to stand for 5 min, the battery is discharged at a constant current with a discharge current of 1.0C until the discharge cut-off voltage is reached, and the discharge capacity at this time is the actual capacity of the battery at 1.0C, and is denoted as C0. At 45 ° C, the secondary battery is subjected to a 1C0 / 1C0 charge and discharge cycle of 100% DOD (100% depth of discharge, i.e., fully discharged after full charge) on a Neware charge and discharge tester. When the number of cycles reaches 600, the cycle is stopped. Then, the secondary battery is charged to 100% SOC, the secondary battery is disassembled, and the thickness of the negative electrode sheet is measured and denoted as H1. The cycle expansion rate of the negative electrode sheet after 600 1C0 / 1C0 cycles at 45°C is (H1 / H0-1) x 100%. 2) Low-temperature lithium deposition performance test for batteries

[0108] First, measure the actual capacity C0 of the battery at 1.0C according to the method in 1). Next, place the battery in an environment of -10°C, charge it at a constant current of xC0 until it reaches the charge cutoff voltage, and then charge it at a constant voltage until the current reaches 0.05C0, leave it for 5 minutes, disassemble the core, and observe the interfacial lithium deposition status. If lithium is not deposited on the negative electrode surface, increase the charge rate and conduct further tests until lithium is deposited on the negative electrode surface. Record the maximum charge rate at which lithium is not deposited on the negative electrode surface, and determine the low-temperature lithium deposition rate. 3) High-temperature cycle performance test of batteries

[0109] First, according to the method of 1), the actual capacity C0 of the battery at 1.0C is measured. Next, in a 60°C environment, the battery is charged at a constant current of 1.0C0 until it reaches the charge cut-off voltage, and then charged at a constant voltage until the current reaches 0.05C0. The battery is then discharged at a constant current of 1.0C0 until it reaches the discharge cut-off voltage. This is regarded as one charge-discharge cycle, and the discharge capacity at this time is the discharge capacity of the first cycle. After that, charge and discharge cycles are performed continuously, and the discharge capacity value during the cycle process is recorded, and the capacity retention rate of each cycle is calculated. When the cycle capacity retention rate is reduced to 80% of the discharge capacity of the first cycle, the number of cycles of the battery is recorded.

[0110] [Table 1]

[0111] [Table 2]

[0112] As can be seen from the comparison results of Examples 1-12 and Comparative Examples 1-6, when the positive electrode sheet contains one or more of layered lithium transition metal oxides and their modified compounds, the negative electrode sheet contains artificial graphite and natural graphite at the same time, and the surface smoothness L of the negative electrode film sheet facing the negative electrode current collector satisfies 40≦L≦50, especially 43≦L≦48, the negative electrode sheet can have low cycle expansion during charging and discharging, and at the same time, the lithium ion transport performance of the negative electrode sheet can be effectively improved, so that the low cycle expansion performance and low temperature power performance of the secondary battery can be improved under the premise that the secondary battery has a high energy density. In addition, the capacity retention rate during high temperature cycle of the battery can also be obviously improved.

[0113] As can be seen from the comparison results of Examples 13 to 25 and Comparative Examples 7 to 12, when the positive electrode sheet contains one or more of the lithium-containing phosphates with an olivine structure and its modified compounds, the negative electrode sheet contains artificial graphite and natural graphite at the same time, and the surface smoothness L of the negative electrode film sheet facing the negative electrode current collector satisfies 45≦L≦55, especially 48≦L≦52, the negative electrode sheet can have low cycle expansion during charging and discharging, and at the same time, the lithium ion transport performance of the negative electrode sheet can be effectively improved, so that the low cycle expansion performance and low temperature power performance of the secondary battery can be improved under the premise that the secondary battery has a high energy density. More preferably, the capacity retention rate during high temperature cycle of the battery can also be obviously improved.

[0114] In addition, as can be seen from the results of Examples 6 to 8 and Examples 18 to 21, when the positive electrode sheet uses a specific positive electrode active material, the negative electrode sheet contains both artificial graphite and natural graphite, and the mass occupancy rate of the natural graphite in the negative electrode active material is within a specific range, it is more advantageous for the battery to simultaneously achieve high low cycle expansion performance, low temperature power performance, and high temperature cycle performance.

[0115] As can be seen from the results of Examples 9 to 12 and Examples 22 to 25, when the positive electrode sheet uses a specific positive electrode active material, the negative electrode sheet contains both artificial graphite and natural graphite, and the compression density and / or areal density of the negative electrode film sheet are within a specific range, it is more advantageous for the battery to simultaneously achieve high low cycle expansion performance, low temperature power performance, and high temperature cycle performance.

[0116] The above description is only specific embodiments of the present application, but the scope of protection of the present application is not limited thereto, and those skilled in the art can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the scope of the present application. Therefore, the scope of protection of the present application shall be equivalent to the scope of protection of the claims.

Claims

1. A secondary battery comprising a positive electrode sheet and a negative electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode film sheet disposed on at least one surface of the positive electrode current collector and having a positive electrode active material, and the negative electrode sheet comprising a negative electrode current collector and a negative electrode film sheet disposed on at least one surface of the negative electrode current collector and having a negative electrode active material, The positive electrode active material includes one or more of a layered lithium transition metal oxide and a modified compound thereof, where the modified compound is a layered lithium transition metal oxide that has been subjected to a doping modification and / or a surface coating modification; the negative electrode active material includes a first material having artificial graphite and a second material having natural graphite; The smoothness L of the surface of the negative electrode film sheet facing the negative electrode current collector satisfies 40≦L≦50, and the smoothness L is measured by the method described in the specification. Secondary battery.

2. The mass occupancy rate of the natural graphite in the negative electrode active material is 10% to 50%. The secondary battery according to claim 1 .

3. The powder compaction density of the negative electrode active material under a pressure of 30000 N is 1.7 g / cm 3 ~1.9g / cm 3 That is, The secondary battery according to claim 1 or 2.

4. the degree of graphitization of the negative electrode active material is 92% to 96%, the degree of graphitization being measured by the method described herein; The secondary battery according to claim 1 .

5. The volume average particle diameter of the negative electrode active material D v 50 is 11 μm to 15 μm; The secondary battery according to claim 1 .

6. The compressed density of the negative electrode film sheet is 1.6 g / cm 3 ~1.8g / cm 3 and / or The surface density of the negative electrode film sheet is 10 mg / cm 2 ~13mg / cm 2 That is, The secondary battery according to claim 1 .

7. A secondary battery comprising a positive electrode sheet and a negative electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode film sheet disposed on at least one surface of the positive electrode current collector and having a positive electrode active material, and the negative electrode sheet comprising a negative electrode current collector and a negative electrode film sheet disposed on at least one surface of the negative electrode current collector and having a negative electrode active material, The positive electrode active material includes one or more of a lithium-containing phosphate having an olivine structure and a modified compound thereof, where the modified compound is a compound that is subjected to doping modification and / or surface coating modification; the negative electrode active material includes a first material having artificial graphite and a second material having natural graphite; The smoothness L of the surface of the negative electrode film sheet facing the negative electrode current collector satisfies 45≦L≦55, and the smoothness L is measured by the method described in the specification. Secondary battery.

8. The mass occupancy rate of the natural graphite in the negative electrode active material is 10% to 50%. The secondary battery according to claim 7.

9. The powder compaction density of the negative electrode active material under a pressure of 30000 N is 1.8 g / cm 3 ~1.9g / cm 3 That is, The secondary battery according to claim 7 or 8.

10. the degree of graphitization of the negative electrode active material is 92% to 95%, the degree of graphitization being measured by the method described herein; The secondary battery according to claim 7 .

11. The volume average particle diameter D of the negative electrode active material v 50 is 15 μm to 19 μm; The secondary battery according to claim 7 .

12. The compressed density of the negative electrode film sheet is 1.5 g / cm 3 ~1.7g / cm 3 and / or The surface density of the negative electrode film sheet is 7 mg / cm 2 ~10mg / cm 2 That is, The secondary battery according to claim 7 .

13. A device comprising the secondary battery according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • High-voltage and high-volumetric-energy-density long-life lithium ion battery and preparation method thereof

    CN106252569A

  • Low-temperature lithium-ion battery

    CN109888368A

  • Anode material for lithium secondary battery, manufacturing method of the same, lithium secondary battery anode using the same, and lithium secondary battery

    JP2005259689A

  • Negative electrode active material for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and method for manufacturing negative electrode material for nonaqueous electrolyte secondary battery

    JP2016152077A